Adjuvant Per-Operative Triamcinolone use in Lumbar Disc Surgery to Alleviate Post-Operative Pain - Ahmed, Syed Adeel; Khan, Habib Ullah; Khan, Awais Ali; Hussain, Zahid; Rasheed, Asif; Shamim, Babar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To study the adjuvant per-operative epidural administration of Triamcinolone in lumbar disc surgery to alleviate post-operative pain. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Neurosurgery, Combined Military Hospital, Rawalpindi Pakistan, from Oct 2021 to Sep 2022 Methodology: Hundred patients aged 20 to 80 years, of either gender, with a single-level prolapsed intervertebral disc and nerve root compression were included and underwent unilateral single-level decompression. A pre-operative MRI scan of the lumbo-sacral spine was done to confirm the diagnosis. All patients initially received conservative management (analgesics and physiotherapy) but failed to respond to it. They were divided into two groups by the lottery method. In Group A, an epidural steroid was administered, while Group B acted as the control. Pain was recorded pre-operatively at 24 hours and then at 1 and 2 weeks post-operatively using the Visual Analogue Scale. Results: The pre-operative median VAS of Groups A and B was not significant at pre-operation. After 24 hours of operation, the median VAS of Group A patients was VAS 3 (1), while in Group-B it was 2 (1), (p-value of 0.001). After 1 week, the median VAS of Group-A patients was 2 (2) and Group- B was 3 (1), with a significant p value of 0.024. After 2 weeks, the median VAS of Group-A patients was 1 (1) and Group B was 2 (1), with a significant p value of 0.015. Conclusion: Intra-operative epidural and foraminal administration of steroids in single-level lumbar disc surgery significantly reduce...